A Quantitative Assessment of Wound Healing With Oxygenated Micro/Nanobubbles in a Preclinical Burn Model. Issue 4 (October 2021) - Sayadi, Lohrasb R.; Rowland, Rebecca; Naides, Alexandra; Tomlinson, Luke; Ponticorvo, Adrien; Durkin, Anthony J.; Widgerow, Alan D.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Burns are devastating injuries, carry significant morbidity, and require long-term treatment or multiple reconstructive procedures. Wound healing and secondary insults caused by burn wound conversion are amendable to therapeutic intervention, where ischemia has been cited as one of the major factors ( Dermatol Surg . 2008;34:1159–1169). Halting injury progression in the zone of stasis is crucial as conversion creates increased burn surface area and depth, leading to local and systemic consequences ( J Burns Wounds . 2006;5:e2). Oxygen-carrying micro/nanobubbles, MNB(O2 ), offer a novel technology that can be used to effectively deliver oxygen to burn wounds and potentially counteract burn wound ischemia. Methods: Topical irrigation with MNB(O2 ) of full-thickness burn wounds on a rodent model (n = 3) was compared against saline-treated controls (n = 3). Tissue structure (reduced scattering coefficient, μs '), oxyhemoglobin concentration (cHbO2 ), and tissue perfusion were quantified over the course of 28 days through spatial frequency domain imaging and laser speckle imaging. Histological samples taken at the end of the experiment were examined for evidence of wound healing. Results: Findings in this preliminary study showed hastened healing with significant differences in spatial frequency domain imaging–measured μs ' during wound healing (days 11–28) in MNB(O2 ) group. The healing "tipping point" seemed to occur at days 9 to 11 with increased collagen organization and increased cHbO2 occurring around that period confirming the gross healing improvements observed. In addition, histological evidence indicated that only the MNB(O2 ) burns had reached the remodeling phase by the end of 28-day study period. Conclusions: These preliminary findings propose the potential of MNB(O2 ) as a topical method for improving burn wound healing.